2019
DOI: 10.3390/su11205816
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Feeding the World

Abstract: The aim of the present research is to provide a comprehensive review about the current challenges related to food security and hidden hunger. Issues are presented according to major factors, such as growing population, changing dietary habits, water efficiency, climate change and volatile food prices. These factors were compiled from reports of major international organizations and from relevant scientific articles on the subject. Collecting the results and presenting them in an accessible manner may provide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(206 citation statements)
references
References 77 publications
2
198
0
6
Order By: Relevance
“…Currently, water resources are suffering from a severe degradation process due to global climate change, demographic growth, the modification in the use of land, and overexploitation derived from economic development [88][89][90][91]. As a result, an increase in the competition for the available water will arise in the near future, which represents a threat to ensuring the resources necessary to guarantee the food supply [92,93]. In this context, the objective is sustainable development, defined as that which satisfies the needs of the current generation without compromising the capacity of future generations to satisfy theirs, considering the environmental, economic, and social dimensions [94].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, water resources are suffering from a severe degradation process due to global climate change, demographic growth, the modification in the use of land, and overexploitation derived from economic development [88][89][90][91]. As a result, an increase in the competition for the available water will arise in the near future, which represents a threat to ensuring the resources necessary to guarantee the food supply [92,93]. In this context, the objective is sustainable development, defined as that which satisfies the needs of the current generation without compromising the capacity of future generations to satisfy theirs, considering the environmental, economic, and social dimensions [94].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, beside the measures existing in the FNS, it is also important to tackle other contextual inequalities shown that this study has shown has a direct influence on food security, including gender disparities, income inequality, education, and regional differences. Furthermore, challenges such as a growing population, climate change, and pandemics [15,16,90], will continue to place pressure on socio-economic systems, ultimately affecting food security and hunger.…”
Section: Discussionmentioning
confidence: 99%
“…The F 2 mapping population, their parents, and three additional genotypes were planted in 2.5 L plastic pots, under the same greenhouse conditions as above, in May 2015. Fresh leaf tissue was sampled from young seedlings individually and DNA was extracted, as described in Gustafsson et al [ 3 ]. The DNA samples of 380 individual plants, comprising 375 F 2 plants, two parents, and three additional genotypes (two field cress and one L. heterophyllum ) were sent to Cornell University for genotyping-by-sequencing (GBS) at the Genomics Facility of the Biotechnology Resource Center [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The demand for plant-based oils is increasing as they play a crucial role in the bioeconomy by serving as a source of raw material for bioenergy, fuel production, and different types of industrial applications [ 1 , 2 ]. In addition, feeding a growing world population requires an increased vegetable oil production for food and feed, which makes oil crop production an important area of agricultural development [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%